Ethical (and Human) Formation Based on Literary Experience: Contributions of Pedagogical Anthropology to Didactics of Literature (2023)
This article summarizes classroom research conducted over five years. It analyzes the effect of literary experience on the ethical education and formation (Bildung) of eleventh-grade students. Through the methodology known as lived experience, the study focused on the possible worlds of classic heroism and existentialism as a life-world, approached through a narrative, hermeneutic, and phenomenological lens, within the framework of pedagogical anthropology. The results demonstrated that the didactics of literature can transcend the discursive nature of reading, transforming it into a question of existence. Thus, it is concluded that this literary experience implies for the readers a leap outside of themselves in pursuit of the generality inherent in formation as a potential effect, prompting them to question their identity and decisions in relation to the other and the others represented in fiction.